Precast Spun Concrete Piers in Road Bridges and Footbridges - Antanas Kudzys; Romualdas Kliukas (The Baltic Journal of Road and Bridge Engineering)
The usability of precast spun concrete members of annular cross-sections as pier shafts for road bridges and footbridges is discussed. The probability distribution of traffic loads is considered, their coefficient of variation is specified. First and second-order load effects for shafts of braced and bracing piers are analysed. The modeling of resisting compressive forces and bending moments of eccentrically loaded spun concrete shafts is considered. The features of mechanical properties of compressed spun concrete specimens reinforced by cold worked high-strength steel bars are presented. A simplified but fairly exact analysis of pier shafts under persistent situations by limit state and probabilitybased approaches is provided. A design of tubular shafts of braced piers using semi-probabilistic and probabilistic reliability verifications is illustrated by a numerical example.